“Obesity, metabolic abnormalities and low-grade inflammation: differencial associations with subclinical atherosclerosis” - González, Sergio; Schiavone, Máximo; Piñero, Federico; Melchiori, Renzo; Brenzoni, Noelia; García, Guido; Alarcón, Pamela; Ferroni, Fabián; Baratta, Sergio; Castellaro, Carlos (Frontiers in Cardiovascular Medicine, 2025)
Background & aimsObesity is associated with an increased risk of atherosclerosis, though recent evidence shows conflicting results. This study aimed to evaluate whether obesity or its association with metabolic abnormalities (MAs) and low-grade inflammation play a more significant role in atherosclerosis development in a primary care population.MethodsA cross-sectional study using data from the Cardiometabolic Risk Factor Registry (CARFARE) at Hospital Universitario Austral included adults undergoing their first healthcare visit for primary cardiovascular prevention. Participants were classified into four groups: metabolically healthy non-obese (MHNO), metabolically healthy obese (MHO), metabolically unhealthy non-obese (MUNO), and metabolically unhealthy obese (MUO), according to the BioShare-EU criteria and body mass index. MAs were defined by the same criteria. Inflammation was estimated through absolute Neutrophil (NEU) count. Atherosclerosis prevalence was analyzed using univariate analysis and multivariable logistic regression models.ResultsAmong 6,735 participants, 23.3% were MHNO, 3.13% MHO, 45.6% MUNO, and 27.9% MUO. MHO subjects were 10.1% of the obese population. In univariate analysis, atherosclerosis prevalence was higher in obese than non-obese individuals (57.1% vs. 52.0%, p = 0.001), but lower in MHNO and MHO compared to MUNO and MUO groups (33.1% and 34.4% vs. 60.4% and 59.5%, p < 0.0001). In multivariate regressions, these latter groups presented an increased adjusted odds ratio (aOR) of atherosclerosis compared to MHNO, while atherosclerosis prevalence was no different between the MHO and MHNO groups [aOR: 0.77 (95% CI: 0.54–1.10)]. Moreover, in a second logistic regression model, MAs [aOR: 1.82 (95% CI: 1.58–2.10)] and NEU were independently associated with atherosclerosis [aOR: 1.08 (95% CI: 1.03–1.14)], while obesity was not [aOR: 0.88 (95% CI: 0.77–1.01)].ConclusionIn this primary care population, the MHO phenotype was not associated with increased atherosclerosis. MAs and inflammation, rather than obesity alone, were independently associated with atherosclerosis. These findings highlight the need for further longitudinal studies to clarify the interactions between obesity and metabolic health in atherosclerosis development.